Development and Evaluation of Augmented Reality-Based Physics Learning Media to Improve Understanding of Wave and Vibration Concepts in Budi Darma University Students - Melda Panjaitan; Siti Nurhabibah Hutagalung (Edumaniora : Jurnal Pendidikan dan Humaniora, 2026)
Physics learning often faces challenges in conveying abstract concepts such as waves and vibrations to students. One innovative solution is the use of Augmented Reality (AR) technology that is able to visualize virtual objects interactively in a real environment. This research aims to develop and evaluate AR-based physics learning media to improve the understanding of wave and vibration concepts in Budi Darma University students.The research method uses a Research and Development (R&D) approach with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of 40 students of the Physics Education Study Program. The research instruments include expert validation sheets, student response questionnaires, and learning outcome tests.The results of the study showed that learning media obtained a validity level of 92.3% with a very valid category. Student response to the media reached 89.7% with the very good category. The increase in learning outcomes was shown by the N-Gain  value of 0.74 which was in the high category.The results of the study show that the use of AR-based learning media is effective in improving students' understanding of the concept of waves and vibrations. AR technology provides concrete visualization that makes it easier for students to understand abstract concepts in physics learning.